Rooting Comparison of Zoysiagrass Cultivars in the Greenhouse - Olayemi Ojeokun; Jack Fry (Kansas Agricultural Experiment Station Research Reports, 2024)
This study evaluated the growth performance of 12 zoysiagrass genotypes under controlled conditions to assess the relationship between rooting characteristics and shoot quality for drought tolerance. The experiment was conducted from May to August 2023 at the Kansas State University Department of Horticulture and Natural Resources, Throckmorton Plant Sciences, Manhattan, KS. Zoysiagrass cultivars were sampled from turf plots and planted in polyvinyl chloride (PVC) pipes filled with calcined clay to facilitate root observation. The experiment used a completely randomized design with five replicates for each cultivar. Weekly data collection included recording maximum root length and shoot quality on a 1 to 9 scale (9 = best, 6 = acceptable), with clippings dried and weighed. Root harvesting occurred from the 14th to the 19th week after planting for further analysis. Root analysis involved scanning and processing with WinRHIZO Pro software, while shoot quality was rated visually. Results showed significant variability among cultivars in root growth patterns, shoot quality, and drought tolerance. Cultivars such as Chisholm and DALZ 1701 demonstrated extensive rooting, while others showed varying degrees of performance. Rooting depths varied among cultivars, indicating differences in root establishment. This study provided valuable insights into the growth performance and potential drought avoidance of zoysiagrass genotypes, facilitating cultivar selection for various landscaping and turf applications.
Keywords: zoysiagrass; drought avoidance; shoot quality; root architecture